Correction: Growing evidence of Plasmodium vivax across malaria-endemic Africa. - PLOS Neglected Tropical Diseases Staff (Public Library of Science (PLoS), 2019)
[This corrects the article DOI: 10.1371/journal.pntd.0007140.].